Luxus Roads. A Rare Diadem with Sapphires from Colonna (Rome) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
A piece of jewellery made of twenty-five gold links in the shape of vertically oriented Hercules knots was found in the sarcophagus of a complex female inhumation—a tomb, with an underground, inaccessible burial chamber, dated to the late 2nd century CE—at Colonna (Rome) in 2011. It is 29 cm long, and all the links were made to receive a second element, which is preserved in seven cases only: seven sapphires, amounting on the whole to 46.2 carats. The complete disappearance of the other eighteen elements and their mounting system strongly suggests that they were pearls. At present, this piece of jewellery is a unicum among the jewels from the Roman empire. Chain necklaces with links in the shape of simple gold Hercules knots—horizontally oriented—alternating with fixing-links bearing gemstones (mostly emerald prisms) are known in Roman jewellery from treasures dating to the 3rd century CE. The length of this item from Colonna and its position in the sarcophagus, close to both the neck and the skull, suggest that the object is related to rare ornaments for the head, attested in 2nd-/3rd-century CE high-ranking female burials in the western Roman empire, which consist of a diadem running above or across the forehead, from ear to ear. The style of the diadem, fitting mostly hairdos dated to the Antonine period, suggests that the diadem from Colonna was created between the early 40s and the mid-60s of the 2nd century CE. Some further observations are finally devoted to the symbolism of the highly decorative shape of the Hercules knot.
Keywords: Roman jewellery; diadem; necklaces; Herculean knot; sapphires; pearls; Roman long-distance trade